Freedom of information: an analysis on the effectivness of Selangor Freedom of Information Enactment 2011 / Raja Hawathul Fahdillah Raja Shah Malik, Raja Azlina Izzah Raja Shahrom and Nur Farah Adela Raub Khan - Raja Shah Malik, Raja Hawathul Fahdillah; Raja Shahrom, Raja Azlina Izzah; Raub Khan, Nur Farah Adela (2012)
The State of Selangor has recently passed the historic Freedom of Information (State of Selangor) 2011 Enactment in its pursuit to promote transparency and accountability. This research aims to study the effectiveness of the Enactment and whether the objectives of the Selangor government in upholding transparency and accountability are truly realised. In order to study the effectiveness of the Enactment, we base our research on three main areas which are on the types of information that can and cannot be disclosed, the procedural requirements under this law and the enforcement of this law. Based on the analysis of the three different areas, we have identified various impediments that are present that could jeopardize effectiveness of the Enactment. For example, the Official Secrets Act 1972 is one of the restrictions that are present in the Enactment. Also, each chapter is organized systematically to highlight on the issues present in the three areas and evidence of each claim. Furthermore, we have conducted comparative studies with United Kingdom and United States on the freedom of information laws in their countries as these countries are well-known to have reputable freedom of information laws. Based on the comparative studies, we conclude that in order to fulfil its objectives, the Selangor government must take measures to enhance the freedom of information law in their state in order to meet the benchmark that has been set by United Kingdom and United States. We have proposed a set of recommendations to improve the Enactment.